DETERMINANTS OF SUCCESS IN HOTEL INDUSTRY: CASE STUDY OF THE REPUBLIC OF SERBIA - Pimić, Miroslav; Marković, Zlatomir; Dinić, Goran; Radivojević, Nikola (Ekonomija - teorija i praksa, 2023)
The paper examines the influence of the key determinants of success in hotel industry in the Republic of Serbia. The research was conducted for the period from 2015 to 2020 on a sample of 23 hotels. The chosen length of the observation period covers a sufficient time interval to cover all heterogeneities in the structure of the observation units, as well as their changes over time, using the dynamic panel analysis model. The adequate sample size was determined by considering the size of the population, the desired level of confidence, and the value of the allowable sampling error. The results of the research have shown that determinants such as business success from the previous period, efficiency of use of total business assets, belonging to a hotel chain, size and increasing hotel concentration index have a positive impact on success in hotel industry. On the other hand, determinants such as hotel indebtedness, operating leverage and hotel age have a negative impact on business success. Determinants such as the quality of environmental protection management and socially responsible hotel business do not have a significant impact on success in hotel industry in the Republic of Serbia.